2014
DOI: 10.1002/cncr.29095
|View full text |Cite
|
Sign up to set email alerts
|

Smoking history predicts for increased risk of second primary lung cancer: A comprehensive analysis

Abstract: BACKGROUND: Tobacco use is the most important risk factor for the development of lung cancer. The objective of the current study was to determine the effect of smoking on the development of second primary lung cancers (SPLCs) and other clinical outcomes after surgery for non-small cell lung cancer (NSCLC). METHODS: All patients who underwent surgery for NSCLC at the study institution from 1995 through 2008 were identified. Rates of SPLC were analyzed based on smoking status and pack-year exposure. Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…A number of studies have investigated the relationship between smoking and outcome of lung cancer patients, but the results are diverse [7,20,21,[31][32][33][34]. The present results clearly supported the conclusion that smoking history can exert a negative influence on RFS and OS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A number of studies have investigated the relationship between smoking and outcome of lung cancer patients, but the results are diverse [7,20,21,[31][32][33][34]. The present results clearly supported the conclusion that smoking history can exert a negative influence on RFS and OS.…”
Section: Discussionsupporting
confidence: 85%
“…The relative risk of lung cancer development is estimated to be 10-to 30-fold in longterm smokers when compared with never smokers [5]. For lung cancer patients, smoking history is associated with diagnosis at a later stage, increased operative mortality, higher rate of local recurrence, and worse long-term survival [6,7]. Furthermore, those who quit smoking develop fewer radiation pneumonitis and infections during radiotherapy, and better response to chemotherapy and targeted therapy [8,9].…”
Section: Original Researchmentioning
confidence: 99%
“…Prior NSCLC is a known risk factor for developing second primary NSCLC at estimated rates of 1-2% per year with increasing tobacco exposure conferring higher risk 6, 7 . Population-based and institutional studies have demonstrated that survivors of head and neck cancer as well as Hodgkin's lymphoma are also at increased risk of developing new primary lung cancer 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with early stage NSCLC are prone to developing a second primary NSCLC at a rate of 1–2%/yr. In the future, targeted nodal assessment could potentially allow for subsequent nodal staging of a second ipsilateral lung cancer, an opportunity which is currently not possible if a full lymphadenectomy has previously been performed 24 .…”
Section: Discussionmentioning
confidence: 99%